Power, Knowledge, and Dissent in Morgenthau's Worldview - Rösch, Felix. author. aut Link
XI, 211 p.
Keywords: This book provides a comprehensive investigation into Hans Morgenthau's life and work. Identifying power, knowledge, and dissent as the fundamental principles that have informed his worldview, this book argues that Morgenthau's lasting contribution to the discipline of International Relations is the human condition of politics.